Challenges for source separation of food waste and turning waste into compost for island-based hotels - Saraswathy Kasavan,; Ahmad Fariz Mohamed,; Sharina Abdul Halim,; Sumiani Yusof,; Rusinah Siron, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The practice of turning food waste into compost among hoteliers in Malaysian islands is still far behind compared to the government’s target of 8% by 2020. This paper aims to identify challenges associated with implementing sources of separation of food waste, turning waste into compost, and proposing relevant actions using island-based hotels on Langkawi Island as a case study. This study adopted the mixed-method approach. The researcher distributed sets of questionnaire surveys to 42 hoteliers, followed by observation and interviews with 23 hoteliers. This study identified the lack of space, existing facilities, expertise, funding, adequate knowledge and support from the hotel management affected the activities separation and composting of food waste at their hotel. The study also suggested five key actions for achieving sustainable food waste management for the hotel sector in Langkawi via separate and compost food waste strategies. Those actions are (1) monitor by establishing a unique team of the hotel staff; (2) cooperation with the contractor of taking waste hotel; (3) systematic waste collection with fixed schedule; (4) waste audit and waste mapping; and (5) adequate infrastructure. This study provides information and guidelines to help hoteliers reduce food waste, save hotel operation costs, and maintain the hotel’s focus on environmentally friendly practices.